The era of the global boiling: Challenges and opportunities for the climatic resilience in the Central American region - Rojas Morales, José Rodrigo (2024)
[Introduction]: In July 2023 was announced the end of planetary warming and the beginning of the era of the global boiling. A climatic anomaly whose unprecedented, aggressiveness will hit the Central American region. [Methodology]: Through technological surveillance tools and data analytics, this study shows a series of challenges and opportunities to meet this threat and move towards resilient regional performance. [Results]: All countries have signed agreements and declaratory public policies for the climate resilience, however historical failures persist as well environmental passives to reduce greenhouse gas emissions and the strong dependence for the use of fossil energy. In contrast, Central America enjoys a matrix of opportunities to increase the climatic ambition, also a diverse mix of renewable energy sources, environmental pay mechanisms and actions to impulse circular economy and the bioeconomy [Conclusions]: The regional agenda fail in connect to a climate shielding to respond the rigors of the boiling era. Regarding those balances, and the scientific evidence, a road map, with climate smart and socially inclusive actions, is proposed. [Recommendations]: For the monitoring, research, and education programs on the boiling era, a regional observatory, on climate resilience (OR2C), is recommended.